Integration of Design Thinking and Quizalize Gamification in Problem Based Learning Numerical Literacy - Zaimatun Ni’mah; Muhtarom Muhtarom; Aryo Andri Nugroho (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
This study aims to develop and explore a Problem-Based Learning (PBL) instructional design integrated with the Design Thinking framework and the gamification platform Quizalize to support students’ numerical problem-solving skills. The study employed a qualitative exploratory design through the five stages of Design Thinking: empathize, define, ideate, prototype, and test. Data were collected through questionnaires distributed via Google Forms, classroom observations, and interviews involving teachers and students from Al Anfal High School, Al Kamal Sarang Islamic High School, and Al Yaqin Sluke High School. During the empathize stage, the researcher identified students’ learning difficulties, classroom needs, and barriers in numerical problem-solving to formulate a more adaptive instructional design. The novelty of this study lies in integrating Problem-Based Learning, Design Thinking, and Quizalize within a human-centered instructional framework that combines contextual problem-solving, interactive gamification, and instant feedback in mathematics learning. The findings indicate that integrating PBL with Design Thinking encourages more student-centered, collaborative learning, while Quizalize provides immediate feedback and strengthens students’ conceptual understanding during problem-solving activities. Overall, the proposed instructional design shows potential for creating more interactive, adaptive, and meaningful numerical literacy learning experiences.